Peran Piala Dunia Fifa 2022 dalam Reformasi Sistem Kafala di Qatar - Mohammad Fallas Taufiqurrohman; Nurwahidin Nurwahidin (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
To successfully host the 2022 FIFA world cup, Qatar is recruiting migrant workers using the kafala system. However, this system was criticized by international organizations because it was considered contrary to human rights, and asked Qatar to reform it. This study aims to discuss the role of the 2022 FIFA World Cup as a catalyst for the reform of the Kafala System in Qatar. This study uses a qualitative methodology through literature studies. The results of this study indicate that the 2022 FIFA World Cup has succeeded in encouraging reform of the Kafala system, both in terms of regulation and implementation. Positive responses were made by various international human rights and labor organizations, although some did not respond and even responded negatively, especially organizations that support LGBT.